Islamic jurisprudence on reproductive technology: a methodological appraisal - Haneef, Sayed Sikandar Shah (Springer, 2014)
Ever since the birth of Louise Brown in the UK, 1978, via in vitro fertilization, and the success story of intracytoplasmic sperm injection (ICSI) in Belgium in 1992 (Inhorn, n.d.) , biomedical technologies have made great strides in assisting not only the infertile couples but even gays and lesbians to have children. Societal responses to this technological advancement by and large have been one of radical support and cautious acceptance. For instance, Western feminists celebrated it as “freeing the Western civilization from the prejudice of morality” (p. 119); Christian Theologies received it with mixed reaction due to a host of moral hazards that it entails for integrity of family and lineage clarity. In the Muslim world, Shi’ah gave it a blanket approval, but the Sunni jurists received it with some caveat. The divergent legal scenario, at microlevel, proves attractive for common Muslims due to a number of anthropological variables such as fulfi llment of a barren male fervent desire for children as a proof of his virility, bringing pride to an infertile wife for proving as reproductive, making polygamy redundant in the case of profoundly in love monogamous couples, etc. (p. 120). At the macro level, however, the dilemma is one of striking a balance between pragmatic consideration of overcoming the problem of infertility and the core principles of sexual purity and lineage clarity within the paradigmatic framework of Muslim family law. Accordingly, this paper proposes to critically review Muslim juridical responses with the purpose of proposing some methodological points for further deliberations.